Analisis Kualitas Layanan dalam Penerbitan Sertifikat Tanah pada Badan Pertanahan Kabupaten Bima - Desy Jein (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2024)
This study aims to determine and analyze the quality of service in the issuance of land certificates at the Bima District Land Agency by using a descriptive research type and choosing a Likert scale questionnaire as a research instrument. The population used in this study is all people who have used the services of issuing land certificates at the Bima Regency Land Agency whose number is unknown (Unknown Population) so as to obtain a sample of 73 respondents. The sampling technique was carried out by purposive sampling method. Data collection techniques used were observation, questionnaires and literature study. Data analysis techniques using validity test, reliability test and one sample t test. the results of the study show that the quality of service in issuing land certificates at the Bima Regency Land Agency is more than 70% of what is expected (good).